Citizen Participation and Municipality Size: Findings in Light of Demonstrations between 2015 and 2017 - Sabioni, Marjorie; Reis, Anderson de Oliveira (Organizações & Sociedade, 2023)
Internet democratization and the natural outspread of news reports and information in social media have been changing citizen’s participation at public sphere. The complexity of the current scenario takes to reflections about how participation practices have been taking place in municipalities. Thus, the aim of the present study is to assess what demonstrations show about municipality size and citizen participation within the Brazilian context. A quantitative-qualitative research schedule was developed in order to do so. The qualitative stage of it aimed at facing information gotten from effective participation in demonstrations carried out in municipalities. Results have shown that structural discrepancies among municipalities translate differences seen in citizen participation. If one takes into account what would be the best municipality size for the democratic exercise, the herein analyzed contextual aspects point toward the coexistence of fruitful environments to participation either in small- or large-sized municipalities, although there is the trend of concrete participation in larger municipalities.